A SmartNIC-Accelerated Monitoring Platform for In-band Network Telemetry - Feng, Yixiao; Panda, Sourav; Kulkarni, Sameer G; Ramakrishnan, K. K.; Duffield, Nick (Proceedings of the ... IEEE Workshop on Local and Metropolitan Area Networks, 2020)
Recent developments in In-band Network Telemetry (INT) provide granular monitoring of performance and load on network elements by collecting information in the data plane. INT enables traffic sources to embed telemetry instructions in data packets, avoiding separate probing or infrequent management-based monitoring. INT sink nodes track and collect metrics by retrieving INT metadata instructions appended by different sources of INT information. However, tracking the INT state in packets arriving at the sink is both compute intensive (requiring complex operations on each packet), and challenging for the standard P4 match-action packet processing pipeline to maintain line-rate. We propose a network telemetry platform in which the INT sink is implemented using distinct (C-based) algorithms on a SmartNIC in the monitoring host, complementing the P4 packet processing pipeline. This design accelerates packet processing and handles complex INT-related operations more efficiently than P4 match-action processing alone. While the P4 pipeline parses INT headers, a general-purpose Micro-C algorithms performs complex INT tasks (e.g. aggregation, event-detection, notification, etc.). We demonstrate that partitioning of INT processing significantly reduces processing overhead vs. a P4-on1y implementation, providing accurate, timely and almost loss-free event notification.